HIPPOCAMPAL CEREBRAL BLOOD FLOW DEPENDS ON SYSTEMIC ENDOTHELIAL FUNCTION IN INDIVIDUALS WITH MILD COGNITIVE IMPAIRMENT: THE TRAIN, THE BRAIN-MIND, THE VESSEL STUDY. (June 2018) - Bruno, R.M.; Pratali, L.; Sicari, R.; Stea, F.; Berardi, N.; Tognoni, G.; Bonuccelli, U.; Ghiadoni, L.; Taddei, S.; Scelfo, D.; Biagi, L.; Tosetti, M.; et al.
Abstract: Objective: Dementia has been recently viewed as a predominantly vascular disorder. Indeed, reduced brain NO availability causes increased ß-amyloid deposition by several mechanisms, including hypoperfusion. We sought to investigate the relationship between cerebral blood flow in the hippocampal and parahippocampal regions (CBF-hipp and CBF-parahipp), crucial areas for memory and processing of non-verbal/spatial information, and systemic endothelial function in individuals with mild cognitive impairment (MCI), a subclinical condition predisposing to dementia. Figure. No caption available. Design and method: CBF-hipp and CBF-parahipp were evaluated by magnetic resonance imaging (arterial spin labeling, GE HDxt 1.5 T Signa Neuro-optimized System) and systemic endothelial function by flow-mediated dilation (FMD) in the brachial artery. Results: Complete data about CBF and FMD at enrollment were available for 66 individuals with MCI and 32 without (non-MCI). The two groups were matched for age (75 ± 5 vs 74 ± 5years, p = 0.22), sex (men 45 vs 50%, p = 0.18) and mean BP (96 ± 10 vs 97 ± 9 mmHg, p = 0.41). FMD was significantly lower in MCI than in non-MCI (2.93 ± 2.18 vs 3.74 ± 2.03%, p = 0.02); CBF-hipp (64.3 ± 9.43 vs 69.5 ± 7.03 ml/100 gr/min, p = 0.002) and CBF-parahipp (66.3 ± 8.02 vs 70.0 ± 8.12 ml/100 gr/min, p = 0.002) were significantly lower in MCI as well. Among MCI, FMD was significantly correlated with CBF- parahipp (r = 0.26, p = 0.03) and CBF-hipp (r = 0.32, p = 0.009). In multiple regression models, including age, sex, mean BP, BMI, brachial artery diameter as confounders, FMD remained an independent determinant of CBF-parahipp (beta = 0.93, r2 = 0.063, p = 0.04) and CBF-hipp (beta = 1.31, r2 = 0.089, p = 0.01). Nor CBF-parahipp (r = −0.13, p = 0.48) neither CBF-hipp (r = 0.05, p = 0.80) were correlated with FMD in non-MCI group. Conclusions: An independent association between hippocampal and parahippocampal CBF and systemic endothelial function is present in individuals with MCI.